Clinical neurocardiology defining the value of neuroscience‐based cardiovascular therapeutics - Shivkumar, Kalyanam; Ajijola, Olujimi A.; Anand, Inder; Armour, J. Andrew; Chen, Peng‐Sheng; Esler, Murray; Ferrari, Gaetano M.; Fishbein, Michael C.; Goldberger, Jeffrey J.; Harper, Ronald M.; Joyner, Michael J.; Khalsa, Sahib S.; et al. (The Journal of physiology, 2016)
The autonomic nervous system regulates all aspects of normal cardiac function, and is recognized to play a critical role in the pathophysiology of many cardiovascular diseases. As such, the value of neuroscience‐based cardiovascular therapeutics is increasingly evident. This White Paper reviews the current state of understanding of human cardiac neuroanatomy, neurophysiology, pathophysiology in specific disease conditions, autonomic testing, risk stratification, and neuromodulatory strategies to mitigate the progression of cardiovascular diseases.